What Drives the Success of a Business Entity or An Organization? A Case Study of Mydin Mohamed Holdings Berhad - Erin Ereena Binti Zaihan; Daisy Mui Hung Kee; Auni Zafira Binti Zarimi; Aina Natasha Binti Kamrol Hisham; Awadh Sahal Awadh Bin Eshaq; Abdulaziz Alkandri; Nidhi Mishra (Journal of the Community Development in Asia (JCDA), 2020)
Mydin, a company that transforms from a small family business to emporium and it is now the largest wholesaler in Malaysia. Mydin sell local and overseas products at affordable prices and cater to a large segment of the Malaysian population. In the hypermarket industry, having the right technology is the key that allows a business to grow, make profit, and successfully compete in the market. Mydin has to provide its products at the right time and at the best price to their customers, whilst ensuring excellent service. Getting information to people at the right time is as crucial. Mydin’s top priority is to ensure the consistency of flow of communication in their supply chain network, from the suppliers, to logistics and warehouse, to the ground staff and management team. Also, Mydin is a wholesaler that meet all consumers’ demand in one building that certainly save their time.